2002
DOI: 10.1074/jbc.m208086200
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor (NGF) Down-regulates the Bcl-2 Homology 3 (BH3) Domain-only Protein Bim and Suppresses Its Proapoptotic Activity by Phosphorylation

Abstract: Bim is a proapoptotic, BH3-domain-only member of the Bcl-2 family that plays a role in death of trophic factor-deprived sympathetic neurons as well as in other paradigms of apoptotic death. We report here that nerve growth factor (NGF) leads to both a slow down-regulation of Bim expression in neuronal PC12 cells and rapid Bim phosphorylation. Both effects appear to be mediated by the MEK/MAPK pathway. An assay for Bim-mediated death revealed that NGF-promoted phosphorylation suppresses the proapoptotic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
173
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(182 citation statements)
references
References 31 publications
8
173
1
Order By: Relevance
“…Biswas and Greene showed that in PC12 cells, NGF can induce phosphorylation of Bim EL and that this is mediated via the MEK/ERK pathway, but the sites in Bim phosphorylated by ERK were not identified in this study. 44 ERK-mediated phosphorylation of Bim EL was also observed by Ley et al in serum-treated fibroblasts. 45 These authors showed that this phosphorylation leads to the ubiquitylation and degradation of Bim via the proteasome, that is, ERK-mediated phosphorylation reduces the stability of the Bim protein.…”
Section: Post-translational Regulation Of Bim and Bad By Phosphorylationsupporting
confidence: 68%
“…Biswas and Greene showed that in PC12 cells, NGF can induce phosphorylation of Bim EL and that this is mediated via the MEK/ERK pathway, but the sites in Bim phosphorylated by ERK were not identified in this study. 44 ERK-mediated phosphorylation of Bim EL was also observed by Ley et al in serum-treated fibroblasts. 45 These authors showed that this phosphorylation leads to the ubiquitylation and degradation of Bim via the proteasome, that is, ERK-mediated phosphorylation reduces the stability of the Bim protein.…”
Section: Post-translational Regulation Of Bim and Bad By Phosphorylationsupporting
confidence: 68%
“…NGF stimulation of PC12 cells was reported to promote the ERK1/2-dependent phosphorylation of Bim L as well as Bim EL , 26 while mutation of Ser44 (Ser104 in Bim EL ) abolished the ERK1/2-dependent phosphorylation of Bim L in FL5.12 cells. 32 Since Ser44 is a prolinedirected site, this suggested that ERK1/2 might directly phosphorylate Bim L .…”
Section: Phosphorylation Of Other Bim Isoforms By Erk1/2: a Question mentioning
confidence: 99%
“…There is some precedent for this in the ability of c-Jun to provide a docking site for JNK, which then phosphorylates the c-Jun dimer partner, JunD, which otherwise fails to bind JNK directly. 40 Despite these reports, 26,32 other studies suggest that Bim L is not phosphorylated following activation of ERK1/2. [29][30][31]33 Aside from caveats regarding different cell types or stimulation conditions, an alternative explanation for this confusion is that another Bim splice variant is actually being studied.…”
Section: Phosphorylation Of Other Bim Isoforms By Erk1/2: a Question mentioning
confidence: 99%
See 2 more Smart Citations